PENGARUH PIJAT KAKI TERHADAP RESIKO JATUH PADA LANSIA : SYSTEMATIC REVIEW: The Influence of Foot Massage on Fall Risk In Elderly: Systematic review - Fanny Dewi Sartika; Andi Masyitha Irwan; Kadek Ayu Erika (LPPM STIKES Pemkab Jombang, 2020)
Background: Falling in the elderly is the most common thing in the elderly. Therefore the elderly need the right intervention to prevent falls. Foot massage is one of the interventions that can help the elderly overcome these health problems. Objective: to assess the effectiveness of foot massage on the balance of the elderly by looking at the duration of time used, the benefits of giving foot massage, instrument of assessment of balance. Methods: The method of searching articles through electronic databases based on PubMed, Science Direct, Wiley Online, and Google Scholars. Result: The results of a review of six articles consisting of two Randomized Control Trial (RCT) studies and four Quasi-Experiment studies discussed the effectiveness of foot massage on balance. Given the length of time for giving foot massage for 10 minutes for each foot, the most effective assessment of fall risk is to use TUG measurement, as well as some benefits of foot massage including increasing balance which is significantly demonstrated by increasing TUG, increasing flexibility and function balance of ankle joints, and can be a viable alternative treatment for performance improving balance, foot ROM, and foot sensation in diabetic patients with peripheral neuropathy. Conclusion: foot massage is very useful to be done in the elderly to improve health status and can prevent the risk of falling Keywords : Foot Massage, Balance, risk of falling, elderly